(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: A retrospective study on neonatal deaths was done in the Medico-Legal Institute of Baghdad. Objective: To differentiate stillbirths from lived ones and to know the causes of death in the last group. Methods: Full autopsy examination was done on all the (17) cadavers of neonates that had been sent to medico-legal institute of Baghdad for six months duration from 1-10-1996 to 31-3-1997, in addition to the required laboratory investigations. The results were converted into tables and figures. Results: Neonatal deaths constituted 6.37% of the total number of pediatric medico-legal mortalities up to 12 years old during the period of the study. The highest percentage of neonatal deaths was in February 1997.The number of the lived births was slightly higher than stillbirths with no significant statistical difference. Bronchopneumonia was the first cause of death in the lived births. In addition to the other results of the study. Conclusion: The prevalence of neonatal deaths is low in Baghdad (During the period of the study) especially the criminal ones with the medico-legal and social importance of that. Key words: Medico-legal, Neonatal, Deaths.